U.S. FOREIGN POLICY TO RESTORE MILITARY RELATIONS WITH INDONESIA AFTER THE REVOCATION OF ITS MILITARY EMBARGO TOWARD INDONESIA - Hariyanti Ningsih sw (2011)
This thesis sought to find out the reasons that led the United States' administration to restore military relations with Indonesia after the revocation of its military embargo toward Indonesia. The research used foreign policy concept, decision making theory, and system theory as theoretical framework of the research. The research started from the hypothesis which argues that the reasons of the United States' administration to restore military relations with Indonesia was to more effectively com